2009
DOI: 10.1007/s00405-009-1141-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of laryngeal findings in users of inhaled steroids

Abstract: The objective of the prospective study is to examine the laryngeal changes by laryngeal videostroboscopy and electromyography (EMG) regarding new-onset dysphonia in asthmatic patients taking inhaled corticosteroids (ICS). Laryngeal changes and electrophysiological status of the laryngeal muscles were evaluated by these methods in 12 patients both at the time of presentation of dysphonia and after cessation of therapy. Laryngeal changes of our patients were mucosal edema, erythema, thickening, adduction deficit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Additionally, there are many reports implicating long‐term inhaled steroid use as a cause of dysphonia 82,262–268 . A theorized mechanism is mucosal deposition of the inhaled corticosteroids and associated mild myopathy of the thyroarytenoid muscle.…”
Section: Guideline Key Action Statementsmentioning
confidence: 99%
“…Additionally, there are many reports implicating long‐term inhaled steroid use as a cause of dysphonia 82,262–268 . A theorized mechanism is mucosal deposition of the inhaled corticosteroids and associated mild myopathy of the thyroarytenoid muscle.…”
Section: Guideline Key Action Statementsmentioning
confidence: 99%
“…Comparisons were conducted to determine differences in gender‐related prevalence of the voice or swallowing problem with the chi‐square test with statistical significance set at P = 0.05. Because the use of inhaled corticosteroids has been associated with an increased prevalence of dysphonia, data regarding the presence or absence of asthma were extracted, and comparisons were also conducted to determine if the presence of active asthma (defined as active if the adult respondent was told by a doctor that the child still has asthma vs. having had asthma, now inactive) was associated with either the voice problem or the swallowing disorder among children …”
Section: Methodsmentioning
confidence: 99%
“…Babu and Samuel et al [14] evaluated the upper aerodigestive tracts of 48 consecutive patients who underwent ICS therapy (with beclomethasone); 20 % of patients experienced voice changes, 46 % had congested erythematous vocal cords, and 8.5 % had adductor palsy with vocal cord bowing. Videolaryngostroboscopic analysis revealed mucosal edema, erythema, thickening, adduction deficits, nodules, irregularity, and supraglottic hyperfunction [15,16]. Our study revealed no macroscopic differences between groups.…”
Section: Discussionmentioning
confidence: 43%
“…Further studies combining mucosal and electrophysiological data are required to address the possibility that the etiology of dysphonia is due to steroid myopathy [15,16].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation